2022
DOI: 10.3390/biomedicines10112688
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Eosinophil Count as a Potential Clinical Biomarker for Clinical Complexity in EGPA: A Real-Life Experience

Abstract: Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is a small-vessel necrotizing vasculitis with multiple organ involvement. Despite improvements in clinical management, biomarkers for organ involvement and disease prognosis are still an unmet need. Methods: EGPA patients referred to our immunology clinic were retrospectively reviewed. Demographic/clinical features, eosinophils, ANCA status, eosinophil cationic protein (ECP) and total serum IgE were evaluated at the baseline. Eosinophils, total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In our previous work, we observed a positive association between BEC and PNS involvement in EGPA patients [ 23 ]. To gain a deeper insight in the value of eosinophils count as a predictive clinical biomarker in EGPA patients, we explored the impact of a progressive increase in baseline BEC on PNS involvement.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In our previous work, we observed a positive association between BEC and PNS involvement in EGPA patients [ 23 ]. To gain a deeper insight in the value of eosinophils count as a predictive clinical biomarker in EGPA patients, we explored the impact of a progressive increase in baseline BEC on PNS involvement.…”
Section: Resultsmentioning
confidence: 94%
“…The peripheral blood eosinophil count is easily obtained, and its use as a diagnostic biomarker of EGPA is well accepted [ 7 , 8 ]. In our previous work, we observed that a high eosinophil count was associated with an increased risk of PNS involvement [ 23 ]. After all, Nishi and coworkers showed that the neurotoxic effect of eosinophils is related to the infiltration of these cells in the endoneurium and epineurium in patients with PNS involvement [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is defined by blood vessel inflammation (i.e., vasculitis) and eosinophil‐rich granulomatous inflammation 377 . Tissue‐infiltrating eosinophils are thought to play a role in the pathophysiology of the disease 378,379 . Two genetically distinct groups of EGPA were suggested as a result of a genome‐wide association study: anti‐neutrophil cytoplasm antibody (ANCA)‐positive and ANCA‐negative EGPA 380 .…”
Section: Vasculitismentioning
confidence: 99%
“…377 Tissue-infiltrating eosinophils are thought to play a role in the pathophysiology of the disease. 378,379 Two genetically distinct groups of EGPA were suggested as a result of a genome-wide association study: anti-neutrophil cytoplasm antibody (ANCA)-positive and ANCA-negative EGPA. 380 The absence of ANCA autoantibodies is associated with increased mortality, lower risk of relapse, reduced vasculitis manifestation, and increased cardiomyopathies.…”
Section: Va Sculitismentioning
confidence: 99%